Single-shot quantitative phase contrast using polarisation-resolved differential phase microscopy - Kalita,R; Lightley,J; Kumar,S; Alexandrov,Y; Garcia,E; Flanagan,W; Neil,MAA; Dunsby,C; French,PMW (2021)
We present a robust, low-cost single-shot implementation of differential phase microscopy utilising a polarisation-sensitive camera to simultaneously acquire 4 images from which the phase gradients and quantitative phase image can be calculated.